Transcriptional control of gene expression during development of Dictyostelium discoideum. - Landfear, S M (1982)
During development of the cellular slime mold Dictyostelium discoideum, approximately 2,000 to 3,000 regulated mRNAs are induced when amoebae enter multicellular aggregates. We used in vitro transcription in isolated nuclei to follow the synthesis of individual mRNA precursors during development; these were quantitated by hybridization to cloned cDNAs or genomic DNAs. Those RNAs that are present at all stages of development--the common RNAs--were transcribed by nuclei from cells at all stages of development. By contrast, those RNAs that are present only after cells begin to aggregate--here called aggregation stage RNAs--were transcribed only by nuclei from cells at the aggregation and postaggregation stages of development. The temporal pattern of in vitro transcription correlated well with the time course of accumulation of different aggregation stage mRNAs. Continued expression of aggregation stage genes normally depends upon cell-to-cell contact or cyclic AMP (cAMP); when cells are disaggregated, the regulated mRNAs are rapidly and specifically degraded. When cAMP is subsequently added to the disaggregated cells, most of the mRNAs reaccumulate. We show here that disaggregation reduced 2- to 10-fold the relative transcription of several aggregation stage RNAs, whereas addition of cAMP to disaggregated cells reinduced the level of regulated gene transcription to values approximating those found in normal postaggregation cells. These results indicate that a representative set of Dictyostelium aggregation stage genes are under transcriptional control; both the transcription and the stability of these mRNAs require either continued cell-to-cell interactions or cAMP.